Highly Durable Superhydrophobic Polydimethylsiloxane/Silica Nanocomposite Surfaces with Good Self-Cleaning Ability - Gong, Xiao (ACS Omega, 2020)
[Image: see text] In this work, we report that superhydrophobic coatings can be prepared by a simple spray-coating technique using readily available materials such as polydimethylsiloxane (PDMS) and hydrophilic and hydrophobic SiO(2) nanoparticles. PDMS can combine with the two kinds of SiO(2) nanoparticles to form a rough structure, which results in superhydrophobicity of the coatings. The prepared superhydrophobic coating has a water contact angle of 156.4° and a sliding angle of less than 5°. Moreover, the coatings can be applied to various substrates such as glass, paper, and plastic. In addition, the coatings show excellent stability and still remain superhydrophobic after ultraviolet radiation, sand abrasion and water impact, tape peeling, and treatment with a strong alkali/acid solution. Furthermore, the superhydrophobic surfaces are proven to be suitable for antifouling and self-cleaning.